1983
DOI: 10.1159/000213129
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of a List-Learning Mnemonic in Three Age Groups

Abstract: The effectiveness of a list-learning mnemonic was assessed across a wide range of ages. Young, middle-aged, and older adults attended a 3-day course in which a modified version of the method of loci was taught. Tests of free recall were administered at the beginning and end of the course. All three age groups displayed significantly better recall following instruction in the mnemonic than they did initially; however, the amount of improvement was less in older subjects than younger ones. These results, though … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…In our own work, we have trained younger and older adults in the Method of Loci to investigate age-related differences in upper limits of plasticity (developmental reserve capacity) in the domain of memory functioning. Adding to earlier results of age differences in word recall with imagery instructions (Hulicka & Grossman, 1967;Mason & Smith, 1977; for a review, see Backman, Mantyla, & Herlitz, 1990), it was found that the magnitude of age differences favoring the young is increased, rather than reduced, through training (Baltes & Kliegl, 1992;Kliegl et al, 1989Kliegl et al, , 1990Rose & Yesavage, 1983;Thompson & Kliegl, 1991). Experiment 2 of Kliegl et al (1989) may serve as a typical example.…”
mentioning
confidence: 82%
“…In our own work, we have trained younger and older adults in the Method of Loci to investigate age-related differences in upper limits of plasticity (developmental reserve capacity) in the domain of memory functioning. Adding to earlier results of age differences in word recall with imagery instructions (Hulicka & Grossman, 1967;Mason & Smith, 1977; for a review, see Backman, Mantyla, & Herlitz, 1990), it was found that the magnitude of age differences favoring the young is increased, rather than reduced, through training (Baltes & Kliegl, 1992;Kliegl et al, 1989Kliegl et al, , 1990Rose & Yesavage, 1983;Thompson & Kliegl, 1991). Experiment 2 of Kliegl et al (1989) may serve as a typical example.…”
mentioning
confidence: 82%
“…Early memory training approaches used mono-factorial techniques such as visualization or organization, cognitive re-structuring, concentration, faces and numbers, mnemonic techniques (Lachman et al, 1992 ), or the loci method (Rose and Yesavage, 1983 ). Ulterior mono-factorial approaches implement not only memory techniques but also train other related support processes such as attention, reasoning, and processing speed.…”
Section: Introductionmentioning
confidence: 99%
“…In previous adult memory-training studies, young adults initially recalled more words than old adults and also benefited more from instruction and practice with elaborative encoding (e.g., Kliegl, Smith, & Baltes, 1989;Rose & Yesavage, 1983). For example, Kliegl etal.…”
mentioning
confidence: 99%